Skill-based differences in the impact of opponent exposure during anticipation: the role of context-environment dependency - Gredin, N. Viktor; Thomas, Joseph L.; Broadbent, David P.; Fawver, Bradley; Williams, A. Mark (Frontiers in Cognition, 2023)
Disclaimer: The authors consent to publish these data. Material has been reviewed by the Walter Reed Army Institute of Research. There is no objection to its presentation and/or publication. The opinions or assertions contained herein are the private views of the author, and are not to be construed as official, or as reflecting true views of the Department of the Army or the Department of Defense. The investigators have adhered to the policies for protection of human subjects as prescribed in AR 70-25.